2018
DOI: 10.1097/prs.0000000000004581
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management and Outcomes of Pierre Robin Sequence: A Comparison of Mandibular Distraction Osteogenesis and Tongue-Lip Adhesion

Abstract: There is a paucity of literature directly comparing tongue-lip adhesion versus mandibular distraction osteogenesis in surgical treatment of patients with Pierre Robin sequence. This study comprehensively reviews the literature for evaluating airway and feeding outcomes following mandibular distraction osteogenesis and tongue-lip adhesion. A search was performed using the MEDLINE and Embase databases for publications between 1960 and June of 2017. English-language, original studies subjects were included. Extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 119 publications
3
61
3
Order By: Relevance
“…[28][29][30] Though a number of decision algorithms have been published, there is a paucity of supporting evidence for these tools. 4 One previous study systematically reviewed all feeding and airway outcomes for children with PRS treated with MDO or TLA. These authors found comparable rates of tracheostomy avoidance; results that are supported by the data presented herein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30] Though a number of decision algorithms have been published, there is a paucity of supporting evidence for these tools. 4 One previous study systematically reviewed all feeding and airway outcomes for children with PRS treated with MDO or TLA. These authors found comparable rates of tracheostomy avoidance; results that are supported by the data presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The selection of MDO versus TLA is controversial, and to date, no randomized trials exist to guide management. 4 Although MDO and TLA have shown comparable outcomes with respect to tracheostomy avoidance 4 and feeding, 17 there remains a paucity of evidence on the effect of TLA and MDO on speech. Although cleft-related speech disorders have been well studied in children with PRS, 18,19 we are only aware of 1 other study that has explicitly examined the effects of surgical airway interventions on consonant production errors (LeBlanc and Golding-Kushner, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While a tracheostomy involves many quality of life considerations and appears to have a higher mortality associated in syndromic PR patients [ 47 ], mandibular distraction osteogenesis (MDO) requires two operations, i.e., one to create mandibular osteomies and apply distraction devices, and a second to remove the devices after completion of distraction and consolidation. Feeding issues may be addressed by glossopexy (tongue–lip adhesion) or MDO [ 48 ]. Due to the individuality of each PR case presentation, no one treatment is best suited to all patients, and each possible intervention is accompanied by benefits and risks that must be carefully evaluated by a multidisciplinary team.…”
Section: Uncertainty Of Diagnosismentioning
confidence: 99%
“…Tongue-lip adhesion (TLA) and mandibular distraction osteogenesis (MDO) have both been described. Studies have shown that MDO is associated with less recurrent obstruction and better oral feeding results [11,12]. However, patients who fail these surgical interventions will ultimately require tracheostomy.…”
Section: Retrognathia and Glossoptosismentioning
confidence: 99%